Feasibility study of the SWITCH implementation process for enhancing school wellness - Senlin Chen; David A. Dzewaltowski; Richard R. Rosenkranz; Lorraine Lanningham-Foster; Spyridoula Vazou; Douglas A. Gentile; Joey A. Lee; Kyle J. Braun; Maren M. Wolff; Gregory J. Welk (BMC, 2018)
Abstract Background There is a need to identify strategies that enhance the implementation of evidence-based school wellness intervention programs in real-world settings. The present study evaluates the feasibility of empowering school wellness leaders to deliver an evidence-based, childhood obesity-prevention program called Switch ™. We specifically evaluated the feasibility of a new implementation framework, based on the robust Healthy Youth Places framework, to increase capacity of school leaders to lead school wellness programming. Methods The SWITCH (School Wellness Integration Targeting Child Health) implementation process was evaluated in a convenience sample of eight Iowa elementary schools. Teams of three leaders from each school attended an in-person school wellness conference followed by five online webinar sessions delivered by two SWITCH team members. The capacity-building and quality improvement process was designed to empower schools to lead wellness change using methods and concepts from the original 16-week Switch ™ program. School wellness leaders completed checklists on two occasions to assess overall school-level implementation as well as setting-level changes in physical education, classrooms, and the lunchroom. Student acceptability of SWITCH was evaluated by the degree of behavior tracking using an online SWITCH Tracker system that promoted self-monitoring. School acceptability and practicality were assessed through an exit survey completed by school leaders. Results All school staff reported satisfaction with the SWITCH implementation process. Reports of school- and setting-level implementation were relatively high (2.0 to 2.8 on a 3-point scale) but student engagement, based on use of the online tracking system, varied greatly over time and across schools. Three high implementation schools had average tracking rates exceeding 70% (range: 72-90%) while three low implementation schools had rates lower than 30% (range = 0-23%). Conclusions This feasibility study supports the utility of the new implementation framework for promoting school and student engagement with SWITCH. Further testing regarding effectiveness and scale-up of this evidence-based school wellness intervention program is warranted.